LncRNA MALAT1 knockdown inhibits apoptosis of mouse hippocampus neuron cells with high glucose by Silencing autophagy - Xiaomei Zhang; Yan Shi; Chao Wang; Kaina Zhang (BMC Endocrine Disorders)
Abstract Background Diabetes mellitus is a fast-growing metabolic disease worldwide, which is often accompanied by various complications in later stages, such as neuropathy and hippocampal neuron damage. LncRNA plays a acts crucial role in the progressional with occurrence of diabetes mellitus, hippocampal neuron damage, and autophagy. MALAT1, a highly conserved lncRNA, is involved in various disease processes. MALAT1 can regulate the damage and inflammation of hippocampal neuron cells, and is highly expressed in high glucose induced hippocampal neuron cells. However, the role of lncRNA MALAT1 in the apoptosis of mouse hippocampus neuron cells with diabetes mellitus remains unclear. Methods Here, an 8-week-old C57BL/6J mice diabetes mellitus model was established. MALAT1 expression in mouse hippocampus tissues was analyzed using qRT-PCR with HT22 cells. CCK-8 assays were applied to measure HT22 cell proliferation. HT22 cell apoptosis with autophagy was analyzed using flow cytometry with TUNEL staining, respectively. The BECN1 and ATG7 protein expressions in HT22 cells were analyzed using Western blotting. Results Bioinformatics analysis in this study found that MALAT1 is highly expressed in the hippocampal tissue of diabetic patients and is associated with the PI3K/AKT signaling pathway. MALAT1 was markedly elevated in mouse hippocampus tissues with diabetes mellitus and high glucose-treated (HGT) HT22 cells. HGT remarkably suppressed HT22 cell proliferation, facilitated apoptosis, and enhanced autophagy biomarkers BECN1 and ATG7 protein; while MALAT1 knockdown remarkably facilitated proliferation, suppressed apoptosis, and reduced BECN1 and ATG7 protein expression in HGT-HT22 cells. Furthermore, activating autophagy could remarkably suppress proliferation, facilitate apoptosis, and enhance BECN1 and ATG7 protein expression in HT22 cells with MALAT1 knockdown. Conclusions The present study verified that MALAT1 knockdown inhibits the apoptosis of mouse hippocampus neuron cells with diabetes mellitus by silencing autophagy.